A Simple Method For Screening Gray Mold Of Castor (Ricinus Communis L.) Under Artificial Conditions (Applied Biological Research, 2016)
Botryotinia ricini (Godfrey) Whetzel, the gray mold pathogen of castor,  inflictsserious crop lossesin short periods. The presentstudywasaimedat to  develop a season-independent screening technique for gray mold in castor.  Conidia from in vitro-raised pure culture of the anamorph Amphobotrys  ricini were sprayed on separated mature as well as immature capsules of 4  castor genotypes (DCS 9, RG 2787, RG 3309 and RG 3216 R), placed in  glass petriplates and incubated at 22-24ºC for 7 days. Genotype DCS-9 was  highly susceptible to the disease, while genotype RG 3216 R exhibited least  susceptibility. Immature capsules were more susceptible to disease than  mature capsules. RNA degradation occurred in treated samples 2 days after  treatment and control gene (UBQ) expression was unaffected till 4 hr post inoculation. Thus a reproducible, lab-based, season-independent, screening  technique using petri-plates and severed castor capsules was developed for  differential gene expression analysis of candidate genes involved in early  infection and elucidating host-pathogen interactions in castor gray mold.
Keywords: Amphobotrys ricini; Botryotinia ricini; castor; gene expression; gray mold disease; sporulation; susceptible